Advancing high-resolution musculoskeletal ultrasound: a histology- and anatomy-driven approach for enhanced shoulder imaging. Part 2: Anterior and lateral shoulder - Tamborrini Giorgio; Micheroli Raphael; Ricci Vincenzo; Becciolini Marco; Garcia-Pompermayer Mario; Gonzalo Andres Serrano Belmar; Müller-Gerbl Magdalena; Margenfeld Felix (Journal of Ultrasonography)
Ultrasonography is a reliable imaging technique for the accurate diagnosis and evaluation of musculoskeletal disorders. Recent developments in ultrasound technology have significantly increased image resolution, making it possible to see anatomical features at almost microscopic dimensions. Current standards for standardized shoulder ultrasonography mostly depend on outdated machine types and configurations that may not fully utilize these high-resolution imaging capabilities. In this article, we give a clear and comprehensive introduction to high-resolution shoulder sonography, using histological and anatomical images from cadavers for comparison. Images collected using contemporary technology are shown, and international standard practices are considered. The examination and normal results are presented in a methodical manner, beginning posteriorly, moving frontally, then more anteriorly, and concluding with a lateral and optional axillary examination. This article focuses on the anterior and lateral shoulder.